Religious Traditions in Modern South Asia - Suthren Hirst, Jacqueline (Taylor and Francis, 2013)
This book offers a fresh approach to the study of religion in modern South Asia. It uses a series of case studies to explore the development of religious ideas and practices, giving students an understanding of the social, political and historical context